2000
DOI: 10.1161/01.hyp.36.1.2
|View full text |Cite
|
Sign up to set email alerts
|

Combinations of Variations in Multiple Genes Are Associated With Hypertension

Abstract: Abstract-The genetic analysis of hypertension has revealed complex and inconsistent results, making it difficult to draw clear conclusions regarding the impact of specific genes on blood pressure regulation in diverse human populations. Some of the confusion from previous studies is probably due to undetected gene-gene interactions. Instead of focusing on the effects of single genes on hypertension, we examined the effects of interactions of alleles at 4 candidate loci. Three of the loci are in the renin-angio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
94
0
2

Year Published

2002
2002
2015
2015

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 126 publications
(103 citation statements)
references
References 24 publications
7
94
0
2
Order By: Relevance
“…Genes regulating the renin angiotensin system have been implicated in the pathogenesis of essential hypertension (47,48). In a cohort of Ghanian hypertensive subjects, we found that there was a significant interaction of GRK4 SNPs (termed FJ) with the SNPs of angiotensin converting enzyme, AT 1 angiotensin receptor, and angiotensinogen (49). In a white population, hypertensives (n ϭ 89) and normotensives (n ϭ 90) differed significantly in disease risk as a function of R65L͞A486V haplotypes (unpublished data).…”
Section: Resultsmentioning
confidence: 93%
“…Genes regulating the renin angiotensin system have been implicated in the pathogenesis of essential hypertension (47,48). In a cohort of Ghanian hypertensive subjects, we found that there was a significant interaction of GRK4 SNPs (termed FJ) with the SNPs of angiotensin converting enzyme, AT 1 angiotensin receptor, and angiotensinogen (49). In a white population, hypertensives (n ϭ 89) and normotensives (n ϭ 90) differed significantly in disease risk as a function of R65L͞A486V haplotypes (unpublished data).…”
Section: Resultsmentioning
confidence: 93%
“…Indeed, there is increasing evidence that epistasis or gene-gene interactions play an important role in determining an individual's risk of complex-trait disease. [23][24][25] However, the identification and characterization of gene-gene interactions have been limited by a lack of powerful statistical methods and a lack of large sample sizes. 26 Several new strategies [23][24][25][26][27][28][29][30] have been developed recently to solve these problems.…”
mentioning
confidence: 99%
“…26 Several new strategies [23][24][25][26][27][28][29][30] have been developed recently to solve these problems. Accordingly, we have adopted these methods [23][24][25][26][27][28][29][30] in the present study to explore the multilocus effects of RAS genes on the development of nonfamilial structural AF.…”
mentioning
confidence: 99%
“…21 Evidence of gene-gene interaction among effects of polymorphisms in these three genes of the RAA system has been reported with respect to occurrence of HTN. 22 This study is the first to report an association between the combined effects of polymorphisms in the AGT and AT 1 R genes, and BP response to a thiazide diuretic.…”
Section: Discussionmentioning
confidence: 77%